The Impact of Gamification on Student Engagement and Learning Outcomes in Mathematics Education - Maryana, Maryana; Halim, Chandra; Rahmi, Hanifatul (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of gamification on student engagement, learning outcomes, and attitudes towards mathematics in middle school education. Utilizing a quasi-experimental design, 200 students were divided into an experimental group, which engaged with a gamified learning platform, and a control group, which followed a traditional curriculum. Pre-test and post-test measures of engagement, academic performance, and attitudes were collected using the Student Engagement Scale (SES), Mathematics Achievement Test (MAT), and Mathematics Attitude Inventory (MAI). The results indicated significant improvements in the experimental group's engagement levels, academic performance, and attitudes towards mathematics compared to the control group. These findings suggest that gamification can effectively enhance educational experiences and outcomes in mathematics by making learning more interactive and motivating. The study underscores the potential of gamification as a valuable pedagogical tool in mathematics education, though further research is recommended to explore its long-term effects and broader applicability.